2013
DOI: 10.1037/a0030234
|View full text |Cite
|
Sign up to set email alerts
|

Emotional faces in context: Age differences in recognition accuracy and scanning patterns.

Abstract: While age-related declines in facial expression recognition are well documented, previous research relied mostly on isolated faces devoid of context. We investigated the effects of context on age differences in recognition of facial emotions and in visual scanning patterns of emotional faces. While their eye movements were monitored, younger and older participants viewed facial expressions (i.e., anger, disgust) in contexts that were emotionally congruent, incongruent, or neutral to the facial expression to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
77
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 46 publications
9
77
2
Order By: Relevance
“…There is also little evidence that physical context (e.g., the background scene) eliminates age differences in emotion perception. Older adults pay more attention to the physical context than young adults [40,41], and attending to congruent contextual information (e.g., a disgusting bathroom scene depicted behind a disgusted face) improves older adults’ emotion perception accuracy [40]. However, the inclusion of context does not fully account for observed age differences in emotion perception accuracy, as younger adults outperform older adults even when congruent contextual information is presented [41].…”
Section: Emotion Perceptionmentioning
confidence: 99%
“…There is also little evidence that physical context (e.g., the background scene) eliminates age differences in emotion perception. Older adults pay more attention to the physical context than young adults [40,41], and attending to congruent contextual information (e.g., a disgusting bathroom scene depicted behind a disgusted face) improves older adults’ emotion perception accuracy [40]. However, the inclusion of context does not fully account for observed age differences in emotion perception accuracy, as younger adults outperform older adults even when congruent contextual information is presented [41].…”
Section: Emotion Perceptionmentioning
confidence: 99%
“…However, they rely heavily on bodily cues when identifying emotions they are uncertain about (Mondloch, 2012). Moreover, compared with younger adults, older adults allocate greater attention toward contextual information relative to facial cues (Noh & Isaacowitz, 2013). This research provides evidence for age-related changes in how individuals combine facial and contextual information in emotion processing.…”
Section: Changes In Processes Underlying the Perception Of Emotionmentioning
confidence: 99%
“…One view holds that features of facial musculature alone are both necessary and sufficient cues for an observer to recognize another’s emotion (e.g., Buck, 1994; Ekman, 1992). The alternative view is that contextual information beyond the face—body postures, gestures, or emotionally charged objects and scenes, for example—is necessary for emotion recognition (e.g., Aviezer et al, 2008; Carroll & Russell, 1996; Noh & Isaacowitz, 2013). There is some empirical support for both of these theories; however, relatively little data exist on possible developmental changes that might integrate these contrasting perspectives.…”
mentioning
confidence: 99%
“…In other words, adding contextual information to the typical emotion recognition task may attenuate age differences in emotion recognition while at the same time increasing the ecological validity of the task. For example, while recent research has suggested that even young adults will use contextual information in their judgment of facial expressions (Aviezer et al, 2008), the effects of context on judgments may be even more pronounced for older individuals (Noh & Isaacowitz, in prep). This would be consistent with studies from the cognitive aging literature suggesting that older adults rely on context as a compensatory strategy (Hess, 2005; Li, Lindenberger, Freund, & Baltes, 2001; Smith et al, 1998), and also that they may be more likely to outsource certain types of processing to external cues (Spieler, Mayr, & LaGrone, 2006).…”
Section: Integrating Context Into the Study Of Aging And Emotion Recomentioning
confidence: 99%